Lithium Insertion Mechanism in Iron‐Based Oxyfluorides with Anionic Vacancies Probed by PDF Analysis. Issue 4 (25th June 2015) - Dambournet, Damien; Chapman, Karena W.; Duttine, Mathieu; Borkiewicz, Olaf; Chupas, Peter J.; Groult, Henri
Abstract The mechanism of lithium insertion that occurs in an iron oxyfluoride sample with a hexagonal–tungsten–bronze (HTB)‐type structure was investigated by the pair distribution function. This study reveals that upon lithiation, the HTB framework collapses to yield disordered rutile and rock salt phases followed by a conversion reaction of the fluoride phase toward lithium fluoride and nanometer‐sized metallic iron. The occurrence of anionic vacancies in the pristine framework was shown to strongly impact the electrochemical activity, that is, the reversible capacity scales with the content of anionic vacancies. Similar to FeOF‐type electrodes, upon de‐lithiation, a disordered rutile phase forms, showing that the anionic chemistry dictates the atomic arrangement of the re‐oxidized phase. Finally, it was shown that the nanoscaling and structural rearrangement induced by the conversion reaction allow the in situ formation of new electrode materials with enhanced electrochemical properties.